PATTERN OF WEIGHTING IN ASES OUTSIDE THE CRIMINAL CODE - Satiman Satiman (Jurnal Hukum Khaira Ummah, 2022)
The basic discussion regarding this research is what is the basis for legislators to determine the "type and number" of crimes that indicate the nature of the disgrace. Are there certain patterns used by legislators in determining matters outside the Criminal Code, especially to carry out their weighting when compared to the general pattern used by forming the Criminal Code. This research was conducted by using the normative juridical method, especially by analyzing the symptoms indicated by the legislators in the criminal threat they stipulated. The results of this study indicate that in Criminal Law, which is the "symbol" of Criminal Law with the identity of the Indonesian nation, there is no particular pattern found in carrying out criminal penalties. Keywords: Weighting of sanctions in cases outside the Criminal Code and criminal threats.